Analysis of Processes (Verbs) in News Discourse: A Systemic Functional Grammar Approach - Amaya García, Marcela A. (Re-presentaciones: Periodismo, comunicación y sociedad, 2008)
In the present work a study of the processes (verbs) in the news speech from a functional point of view is carried out (Halliday, 1994). Concretly, the occurrence is analyzed of these as linguistic feature associated with the structural internal characteristics of the informative news genre, this is, the news. It splits of a representative sample extracted from the diary "La Tercera", following the conceptual modals raised by the journalistic theory (Warren, 1975, between others). The results of the observed units point, on one hand, at the preferential use on the part of the textual producer of the material processes, which refer to the physical world or to the reality and, for other one, to the unutilization of attributive, intensive and circumstantial processes of nature.